Annual Asia Partner Reports, Year 1. - Feed the Future Innovation Lab for Nutrition. (Tufts University. Tisch Library., 2016)
A compilation of the Nutrition Innovation Lab's partners' 2011 annual reports submitted USAID, honing in on their specific contributions to the Innovation Lab's projects, efforts, and outcomes. Partners include John Hopkins School of Public Health, Harvard School of Public Health, Purdue University, Tuskegee University, and DAI. Annual Report, POSHAN, Stunting.; Nutrition School: Annual Reports.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy